一种舆情数据的新闻主体识别方法及系统 (2024)
本发明公开了一种舆情数据的新闻主体识别方法及系统，方法包括将新闻舆情数据通过AI大模型进行主体名称识别，得到舆情特征识别结果；其中，AI大模型通过基于上下文指令对ChatGPT模型进行数据训练而得到；通过对舆情特征识别结果进行字符串匹配，判断舆情特征识别结果中是否存在新闻主体，若不存在，则输出未识别出主体的提示信息；若存在，则将舆情特征识别结果进行无效信息剔除，得到主体简化数据，并对主体简化数据进行主体数量判别分割，获得主体简化名称；通过公共子序列最优匹配策略，将主体简化名称与预先构建的公司知识库进行匹配，输出新闻主体名称识别结果。本实施例实现在海量新闻舆情信息中高效提取主体公司名称，提高主体识别的精准性。 The invention discloses a news subject recognition method and system for public opinion data, and the method comprises the steps: carrying out the subject name recognition of the news public opinion data through an AI large model, and obtaining a public opinion feature recognition result; wherein the AI large model is obtained by performing data training on a ChatGPT model based on a context instruction; performing character string matching on the public opinion feature recognition result, judging whether a news subject exists in the public opinion feature recognition result or not, and if not, outputting prompt information that the subject is not recognized; if the public opinion feature recognition result